2020
DOI: 10.2196/preprints.22361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intimate Partner Violence and Electronic Health Interventions: Systematic Review and Meta-Analysis of Randomized Trials (Preprint)

Abstract: BACKGROUND Intimate partner violence (IPV) is a major public health concern. Electronic health (eHealth) interventions may reduce exposure to violence and health-related consequences as the technology provides a safe and flexible space for the target population. However, the evidence is unclear. OBJECTIVE To examine the effect of eHealth interventions compared to standard care on reducing intim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Clear consensus for standardized indicators and measurement tools does not yet exist. The research we observed during our review reflected this, and at least one of the reviews explicitly noted the lack of harmonized outcome indicators(Linde et al, 2020). Ironically, the observation about the lack of a lack of homogeneity among the outcome measurements, an obstacle to making analytical comparisons, was also noted in a review of ICT used for SGBV in HIC as well(El Morr, 2020, p. 1)…”
supporting
confidence: 52%
See 3 more Smart Citations
“…Clear consensus for standardized indicators and measurement tools does not yet exist. The research we observed during our review reflected this, and at least one of the reviews explicitly noted the lack of harmonized outcome indicators(Linde et al, 2020). Ironically, the observation about the lack of a lack of homogeneity among the outcome measurements, an obstacle to making analytical comparisons, was also noted in a review of ICT used for SGBV in HIC as well(El Morr, 2020, p. 1)…”
supporting
confidence: 52%
“…Linde summarized the impact of all the included studies (which included studies conducted in HIC) as finding "no evidence from randomized trials of a beneficial effect of eHealth interventions on overall IPV; physical, sexual, or psychological violence; or depression and PTSD. However, the types of outcomes and how they were measured were very heterogenous across trials, which limited the possibility of pooling results and identifying patterns across studies" (Linde et al, 2020).…”
Section: Modes Of Ict Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…If, as inflation predicts (e.g. Linde 2005), and observations indicate (e.g. Bouchet et al 1993;Nusser, Dekel & Yahil 1995;Planck Collaboration XVII 2016;Planck Collaboration IX 2020), the primordial density field is Gaussian, and statistically homogeneous and isotropic, its latetime power spectrum and the distribution of haloes that form in a sufficiently large volume are fully determined by the laws of physics, and the universal cosmological parameters (e.g.…”
mentioning
confidence: 99%